2020
DOI: 10.15421/332005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonstoichiometric defects and Cr ions on the photoconductivity of Bi12SiO20 crystals

Abstract: The results of an experimental study of the effect of nonstoichiometric defects in oxygen and the Bi:Si ratio, as well as Cr ions, on the photoconductivity of Bi12SiO20 crystals are presented. It is shown that varying the annealing conditions allows one to modify the spectral distribution and quantitative characteristics of photoconductivity substantially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 3 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…[17] It has been reported that the Cr ion replaces the Si 4þ tetrahedral site but may occur in both Cr 4þ and Cr 5þ states. [18,19] The ionic radii of Cr 4þ and Cr 5þ in tetrahedral site are 55 and 48.5 pm, respectively. It replaces Si 4þ which has lower ionic radii of 40 pm in the tetrahedral site.…”
Section: Crystal Structurementioning
confidence: 99%
See 3 more Smart Citations
“…[17] It has been reported that the Cr ion replaces the Si 4þ tetrahedral site but may occur in both Cr 4þ and Cr 5þ states. [18,19] The ionic radii of Cr 4þ and Cr 5þ in tetrahedral site are 55 and 48.5 pm, respectively. It replaces Si 4þ which has lower ionic radii of 40 pm in the tetrahedral site.…”
Section: Crystal Structurementioning
confidence: 99%
“…On close examination of the transmission spectra, it appears that this may be attributed to the defect-related absorption band close to the band edge, possibly originated from the charge imbalance when Cr in trivalent state replaces Si 4þ . [18,19] 3.6. Refractive Index…”
Section: Emission Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations